A Comparative Study of Middle School’s Ethical Climate in Indonesia - Rahmania Utari; Wiwik Wijayanti; Cepi Safruddin Abduljabar; Maria Dominika Niron; Tina Rahmawati; Udik Budi Wibowo (Ethics in Progress, 2024)
This study aims to: (1) describe the level of ethical climate at middle schools, (2) compare the ethical climate at public schools based on teacher-student analysis, public school-private school analysis and district level analysis, and (3) explore findings to gain an intensive understanding of issues within the ethical climate realm at middle schools. Using a mixed-method approach with both quantitative and qualitative components, the research involved 360 participants across four schools (288 students and 72 teachers). Proportional stratified random sampling and a modified questionnaire based on Schulte’s instruments were used for collecting data during the quantitative phase. During the qualitative phase, the data were gathered through focused group discussions (FGDs), involving 20 teachers and 4 school principals. The results showed that the level of ethical climate at middle schools in the region was high at an average score of 3.285 out of 4 (82.125%). Notably, there were discrepancies between teacher and student perspectives. The study confirmed that the perceptions were significantly different between teachers and students and among the four schools. However, no discernible disparity in the ethical climate was found between public and private schools. In the qualitative phase, the study highlighted the imperative of discouraging negative behaviors, specifically teenage delinquency and bullying. Socioeconomic disparities were barriers to student interaction, prompting the recommendation for schools to intensify character building for consistent positive behavior. The promotion of honesty was particularly emphasized to mitigate cheating and bullying.